Tipe Nilai, Interaksi Antartipe Nilai, Konflik, dan Gaya Pengelolaan Konflik Individu Dewasa Muda di Jakarta yang Saling Berbagi Tempat Tinggal - Agatha N. Ardhiati; Soesmalijah Soewondo; Fitri Fausiah (Jurnal Ilmiah Psikologi MIND SET, 2012)
House-sharing is a phenomenon that is often found in relatively expensive cities such as Jakarta. By sharing a residence, an individual can save on personal expenses and allocate them to meet other needs. The decision to live together, although been made with full consideration, including the value equation, the difference between the individuals is still inevitable, which can result in a dispute or conflict. This study aims to obtain descriptions about value type, value type interactions, conflict, and conflict management style within these individuals. To investigate this, mixed-method approach had been used with sequential explanatory strategy, which carried out the quantitative data collection and analysis using Schwartz Personal Value (SPV) Questionnaire and The Thomas-Kilman Instrument (TKI), then performed the qualitative data collection and analysis. Participants of this study were the occupants of 2 (two) different residences. The result showed that the interaction between individual values may establish harmony or conflict relationship. Conflicts that arise from conflicting value types are managed by different style.